Electronic institution : an e-contracting platform for virtual organization - Henrique Lopes Cardoso (2006)
Automated tools that assist contract drafting are mostly focused on the representation of contract documents. Multi-agent systems have been ap-plied in the e-business domain, namely for information discovery and contract negotiation. Work on contract monitoring and enforcement is less explored. In this paper we start from these two observations to expose our efforts towards the development of tools that enable the computational representation of con-tracts and furthermore their monitoring and enforcement. We are mostly inter-ested in Virtual Organization settings, where groups of agents representing dif-ferent business entities form consortiums that must be regulated by appropriate norms. We are pursuing the concept of an Electronic Institution as a platform providing a normative environment and a set of e-contracting related services. Within this environment, contracts are represented through norms. We intend to test the applicability of our approach through illustration with case-studies and comparison with other contract representation formalisms.